Improving Porosity Calculation Methods and Proposing a New Model Universally Applicable to Large- and Medium-sized Planetary Objects - Imre Kisvárdai; Ákos Kereszturi (The Astrophysical Journal, 2025)
Our work was aimed at the improvement of two main already existing methods of porosity calculation on a planetary scale in order to expand these methods to be applicable to exoplanetary interiors. In addition to implementing some improvements in the used approach, we also wanted to provide a new, more sophisticated model with the combination of the two base models. Utilizing our combined model we aimed to provide results regarding the porosity structure of the interior of four planetary bodies of the solar system (Enceladus, Earth, Mars, and the Moon), chosen as case studies. Taking a method that is based on fitted functions to experimental data from geological environments, and a separate method based on the temporal evolution of planetary interiors governed by thermodynamic processes, we developed a combined model, which incorporates the advantages of both base models. The proposed new model produced a pore compaction depth of 62.52 km for the core of Enceladus, 4.5 km for Earth, 19.96 km for Mars, and 32.51 km for the Moon. Moreover, we have discovered differing trends between the effect of changes in geothermal gradient and surface temperatures across planetary objects of different sizes.